PENINGKATAN MOTIVASI BELAJAR MELALUI MULTIMEDIA PEMBELAJARAN PENDIDIKAN AGAMA ISLAM DALAM MENINGKATKAN MOTIVASI BELAJAR SISWA (Studi Kasus di SMA Al Hikmah Tenjolaya Bogor) - Muhammad Jihad Al Fath; Sholihul Ansori (JOURNAL SAINS STUDENT RESEARCH, 2024)
This research is motivated by the lack of teachers in using multimedia learning of Islamic Religious Education at SMA Al Hikmah Tenjolaya Bogor. The use of conventional learning models creates a sense of boredom for students, so that students lack the motivation to continue learning. Because in the learning process there needs to be a supportive atmosphere and learning model, so that students will be more effective and efficient in learning. The research that the author uses in this thesis uses qualitative research, qualitative research is field research conducted on objects or places. The type of research is a case study, In this study the authors used primary data sources, namely, in the form of interviews that came from related parties. Such as, principals, PAI teachers, and students. From the results of this study it can be concluded that the use of Islamic Religious Education learning multimedia can be a major factor in student learning motivation. By applying the use of multimedia that can show ppt, videos, and pictures in learning, it can help students better understand the material delivered by the teacher and learning becomes effective. In addition, the use of learning multimedia also has a positive impact on students and makes it easier for teachers to achieve the desired learning objectives. Besides having advantages, the use of learning multimedia at SMA Al Hikmah Tenjolaya Bogor has disadvantages, namely the lack of facilities and infrastructure available at school.